Tri Hita Karana and Islamic Ethics: Bridging Universal Values for Social Harmony and Environmental Sustainability - Hisyam, Mohamad Ali; Damyati, Akhmad Rofii; Hambali, Khadijah Binti Mohd Khambali @; Toksöz, Hatice (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
Tri Hita Karana (THK) is a fundamental principle of Hindu philosophy, particularly influential in Bali that emphasizes harmony in three interrelated realms: with the divine (Parahyangan), with fellow human beings (Pawongan), and with nature (Palemaha). This balance has fostered social cohesion within Hindu communities, promoted environmental stewardship, and served as a broader model for societal harmony and sustainability. While rooted in Hinduism, THK resonates with universal values that transcend religious boundaries. However, as Muslims seek to adopt practices inspired by THK, theological differences may arise, particularly regarding acts of worship. This study explores the compatibility of THK with Islamic teachings, particularly in the areas of social and environmental ethics, drawing on the work of scholars such as Mutawalli Sha‘rawi. Both Islam and Hinduism emphasize obedience to God, human welfare, and environmental responsibility. However, differences in worship must be respected. Muslims can embrace THK’s principles of social and environmental responsibility within the permissible framework of Islamic doctrine while avoiding practices associated with Parahyangan. This approach promotes interfaith understanding while enabling collective efforts toward social harmony and environmental stewardship.